2007
DOI: 10.1016/j.gene.2006.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Genomic heterogeneity in the density of noncoding single-nucleotide and microsatellite polymorphisms in Plasmodium falciparum

Abstract: The density and distribution of single-nucleotide polymorphisms (SNPs) across the genome has important implications for linkage disequilibrium mapping and association studies, and the level of simple-sequence microsatellite polymorphisms has important implications for the use of oligonucleotide hybridization methods to genotype SNPs. To assess the density of these types of polymorphisms in P. falciparum, we sampled introns and noncoding DNA upstream and downstream of coding regions among a variety of geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…Further, approximate equal abundance of mono-and di-repeats with length ≥10 NT and ≥15 NT reflects high length variability in these repeat types. The results corroborate earlier studies where long repeat types were found to be more stable than the short ones (Volkman et al 2007). The present study also notifies that mono-(in P. vivax and P. knowlesi) and di-repeats (in P. falciparum) can serve as perfect molecular marker in population genetic studies as these repeat types show high length variability in individual genomes.…”
Section: Discussionsupporting
confidence: 92%
“…Further, approximate equal abundance of mono-and di-repeats with length ≥10 NT and ≥15 NT reflects high length variability in these repeat types. The results corroborate earlier studies where long repeat types were found to be more stable than the short ones (Volkman et al 2007). The present study also notifies that mono-(in P. vivax and P. knowlesi) and di-repeats (in P. falciparum) can serve as perfect molecular marker in population genetic studies as these repeat types show high length variability in individual genomes.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, these TRs were inherited in a Mendelian fashion in progeny of a genetic cross indicating short-term stability through meiosis and mitosis (data not shown). More extensive studies will be required to determine the stability of VNTRs and the rate at which these mutations occur, however, other studies indicate that indels/TRs provide at least as much polymorphism as SNPs in P. falciparum (Volkman et al 2007a, b). …”
Section: Discussionmentioning
confidence: 99%
“…This presumably reflects the influence of diversifying selection exerted on genes by factors such as host immunity and drug selection. [4][5][6][7][8]. High rates of recombination, such as that observed among African P. falciparum strains [7], will tend to obscure the linkage between ancestral traits.…”
Section: Genomic Studies Using Polymorphisms To Identify Resistance Locimentioning
confidence: 99%